Of local people and investors: The dynamics of land rights configuration in Tanzania - Emmanuel Sulle (Danish Institute for International Studies (DIIS), 2017)
This paper analyses the configuration of land rights among different users of land at various levels of land administration. It discusses the implementation of Tanzania's land policy reform. The key rights explored in the paper include the rights of both small-scale producers (farmers and pastoralists) and large-scale investors to agricultural land. The paper explores how the state defines, allocates, protects and compensates for land when it appropriates such rights. At the heart of this paper are the formal, informal and procedural rights that provide for and protect the rights of small-scale producers and investors, and the compensation offered to those who give up their land for investment purposes. The paper also discusses how these formal, informal and procedural rights are configured during the investment negotiation and implementation phases of land deals. It argues that, while the proposed draft National Land Policy of 2016 tries to address the core problems related to the poor coordination and implementation of the earlier Land Policy of 1995 due to a lack of political will, which derailed its performance, the current draft also has significant shortcomings. The ongoing land policy reform provides an opportunity to address the current challenges in the land sector, but it is only likely to be successful if the process becomes more inclusive, prioritizes small-scale local producers, and addresses issues of inequality and ethnic and class-based struggles over land in the country.
Keywords: 330